Benjamin Harrison - Calhoun, Charles W. 1948- (Times Books, Henry Holt and Company, 2005)
A portrait of the presidency of Benjamin Harrison describes his rise to political power, his controversial victory over Grover Cleveland in the 1888 election, the successes and failures of his administration, his loss to Cleveland in the 1893 election, and his historical legacy.
Includes bibliographical references and index
Keywords: Harrison, Benjamin -- 1833-1901; Politik; Presidents -- United States -- Biography; Präsident; USA; United States -- Politics and government -- 1889-1893; Biografie